AI in Talent Development : capitalize on the ai revolution to transform the way you work, learn and live - Meacham, Margie (Association for Talent Development : Association for Talent Development, 2020)
Creating Transparent AI From agriculture to transportation, entertainment to medicine, and banking to social media, artificial intelligence (AI) is changing how humans do practically everything. We experience AI in our daily lives through our fitness trackers, home digital assistant systems, and curated news services, to name a few examples. For talent development, this is no different. The fields of artificial intelligence and talent development have been on a collision course for decades, and their convergence has already occurred. It has just taken many in our profession some time to recognize this fact. On the horizon, AI-powered innovations are transforming the workplace and the role of the talent development professional, affecting recruiting to training to compensation. As such, there are actions TD professionals should take now to prepare ourselves and our organizations for the evolving AI revolution. In AI in Talent Development, Margie Meacham describes the benefits, uses, and risks of AI technology and offers practical tools to strengthen and enhance learning and performance programs. In layman's terms, Meacham demonstrates how we can free time for ourselves by employing a useful robot "assistant," create a chatbot for specific tasks (such as a new manager bot, a sales coach bot, or new employee onboarding bot), and build personalized coaching tools from AI-processed big data. She concludes each of the six chapters with helpful tips and includes a resource guide with planning tools, templates, and worksheets. Meacham dispels fear of AI's black box-the term used to describe its unknowability and opacity-and points out ways AI can help us be better at creativity and critical thinking, what we humans do best.